Review of Corporate Governance as Part of Strategic Decision Making (Survey of State-Owned Companies Listed on the Indonesia Stock Exchange for The Period 2016-2019) - et. al., Muhammad Ali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the dimensions of Good Corporate Governance in terms of managerial ownership, institutional ownership, and independent commissioner in state-owned companies listed on the Indonesia Stock Exchange (BEI) for the period 2016-2019.This research method uses descriptive statistical analysis while the population of this study is state-owned companies listed on the Indonesia Stock Exchange (BEI) in 2016-2019. The sampling technique in this study used purposive sampling and obtained 19 companies with a study period of 4 years in order to obtain 76 sample dataThe results of this study indicate that managerial ownership as seen from the proportion of the number of shareholders from management who actively participate in company decision making (directors and commissioners) is below 1% and tends to decrease. Institutional ownership as seen from the shares of companies owned by institutions or institutions (insurance companies, banks, investment companies and other institutional ownership) is still the majority above 90%.The independent commissioners as seen from the proportion of the number of independent commissioners compared to the number of commissioners has reached 39% in supervising company management.